2008
DOI: 10.1017/s0265021507003110
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine and postoperative shivering in patients undergoing elective abdominal hysterectomy

Abstract: Intraoperative dexmedetomidine infusion may be effective in the prevention of post-anaesthetic shivering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 32 publications
3
78
1
1
Order By: Relevance
“…19 The findings of our study are in accordance with Elvan et al who found that shivering was prevented when dexmedetomidine infusion was given in patients undergoing an elective abdominal hysterectomy. 20 Coskuner et al also did not found shivering with the same dose used in our study. 21 Whereas Bicer et al found shivering in 15% of patients with dexmedetomidine following general anesthesia, whereas it was reported in 55% patients who were given placebo.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…19 The findings of our study are in accordance with Elvan et al who found that shivering was prevented when dexmedetomidine infusion was given in patients undergoing an elective abdominal hysterectomy. 20 Coskuner et al also did not found shivering with the same dose used in our study. 21 Whereas Bicer et al found shivering in 15% of patients with dexmedetomidine following general anesthesia, whereas it was reported in 55% patients who were given placebo.…”
Section: Discussionsupporting
confidence: 74%
“…8 Dexmedetomidine acts as antishivering agent by means it being a α-2-adrenergic receptor agonist with potent effects on the central nervous system. 9 We carried out this study to compare between an intravenous low dose of ketamine and an intravenous infusion of dexmedetomidine for prevention of intraoperative shivering during spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, dexmedetomidine was shown to increase the temperature range without triggering thermoregulatory defenses through stimulation of central α2-adrenergic receptors, thereby decreasing the central thermoregulatory threshold for shivering. [20][21][22] It is possible that the anti-shivering effect of intrathecal dexmedetomidine may be caused by decreasing shivering threshold.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23] Moreover, robust data on safety of use of IV dexmedetomidine in parturients is largely lacking. Callaway et al reported a decreased incidence of shivering with use of i.v.…”
Section: Discussionmentioning
confidence: 99%
“…3,9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] Other control agents included fentanyl, [33][34][35][36] remifentanyl, 37,38 meperidine, 15 midazolam, [39][40][41] propofol, 43,44 ketamine, 45,46 tramadol, 24,47 clonidine, 42 propacetamol, 48 and buprenorphine 49 ( 8 were reported in the 39 included trials, and all studies reported every endpoint mentioned in the Methods section (reporting bias). 8 however, some bias 8 may exist in of the two trials, 27,32 as the length of surgery was not clear.…”
Section: Study Characteristicmentioning
confidence: 99%